Effects of deacetylation of konjac glucomannan and high temperature treatment on rheological and textural characteristics of threadfin bream surimi gels - Supissara Phisutthigoson; Warangkana Sompongse (Agriculture and Natural Resources, 2021)
The effects were investigated of different degrees of deacetylation (DD) of konjac glucomannan (KGM) on the rheological and textural characteristics of threadfin bream surimi gels subjected to high temperature treatment. Different DD percentages of KGM (0%DD, 64%DD, 94%DD) were added with 2% surimi by weight and the samples were coded as SD0, SD1 and SD2, respectively. The control sample had no added KGM. In a temperature sweep test (4–120°C), the surimi with or without deacetylated KGM had higher storage modulus (G′) and loss modulus (G′′) values than that of the control at all temperatures. SD2 had the highest G′ value at temperatures of 22–57°C and above 95°C. SD2 had the highest gel strength but the lowest expressible water content. During heating, the 94%DD KGM could readily disperse through the protein gel matrix, and after cooling it could increase the G′ value of the surimi gel. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis patterns suggested that high temperatures may enhance myosin polymerization, as all samples completely lacked the myosin heavy chain band. Scanning electron microscopy imaging of SD2 showed a more dense and more uniform microstructure than for the other samples.